2009
DOI: 10.1039/b907362k
|View full text |Cite
|
Sign up to set email alerts
|

Iron-catalyzed thioetherification of thiols with aryl iodides

Abstract: FeCl(3) in combination with bisphosphine ligands represents an efficient catalyst system for the cross-coupling of aryl- and alkyl thiols with aryl iodides, a broad spectrum of functional groups can be tolerated during the catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…613 They employed iron(III) chloride as catalyst but replaced the DMEDA ligand by Xantphos. Thus, a number of alkyl aryl thioethers could be obtained in high yields.…”
Section: Scheme 323mentioning
confidence: 99%
“…613 They employed iron(III) chloride as catalyst but replaced the DMEDA ligand by Xantphos. Thus, a number of alkyl aryl thioethers could be obtained in high yields.…”
Section: Scheme 323mentioning
confidence: 99%
“…The preparation of thioethers has been under consideration and widely studied in recent years using palladium [23], nickel [24], cobalt [25], copper [26] and iron salts [27] as catalysts. Migita et al [28] first reported the coupling of aryl halides with thiols using Pd(PPh 3 ) 4 as a catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…12 Moreover, in most cases, the catalytic systems comprised of expensive catalysts, phosphine-based ligands, moisture sensitive bases, and organic solvents. 13 On the other hand, in recent years the design of green chemistry approaches for the thiol S-arylation reactions has received much attention. The use of water as a solvent for organic reactions is of high practical value, since water is cheap, non-toxic, safe, and environmentally benign as compared to organic solvents.…”
Section: Introductionmentioning
confidence: 99%